Evaluating key institutional perspectives for the sustainability of the proposed Ermita heritage zone - Calizo, Antonio Andre D.; Gomez, Jose Edgardo A. (Quezon City School of Urban and Regional Planning, University of the Philippines Diliman, 2018)
This study was conducted in light of the proposals made in 2014 to declare Ermita in Manila as a "Heritage Zone" in accordance with the Natural Cultural Heritage Act of 2009 (Republic Act No. 10066). The proposal specifically covered the University of the Philippines (UP) Manila complex, the Supreme Court (SC), the National Museum (NM) complex, the Manila City Hall, the Manila Post Office and the Metropolitan Theater. Given the nature and consequences of such a declaration, matters of planning, implementation and sustainability need to be addressed. Five (5) Ermita-based institutions - the Supreme Court, Court of Appeals, Department of Justice, UP Manila and the Philippine General Hospital (PGH) were made subjects of this study. Research focused on key institutional perspectives to answer questions on (1) the Protection and Stewardship of their cultural or historic and significant properties, and cultural heritage as a whole. and (2) the prospects of the institutions entering into partnerships to address common concerns on cultural heritage, their shared public space in Ermita and on this proposed Heritage Zone as well. How are they as Protectors and Stewards of (their) heritage, i.e. their built heritage, archival materials, marked structures and historical monuments? A scoring system was formulated to draw out results from the qualitative data gathered. In particular, a scoring spectrum was adopted in an attempt to show and explain how these dimensions are to be characterized, identified and evaluated accordingly - the existence or presence, level, range, quality and/or breadth or coverage of these categories. Qualities defining their awareness and knowledge; actions or inaction; competence, and the matter of policies, rules and programs were also covered. The second objective of the Study looked into how these institutions engaged their external environment or larger physical context/s. Precedents and new prospects of cooperation for common concerns in their shared or common public space were looked into as well. The study attempts to view and analyze their public space concerns in relation to what is termed "urban commons" and how it affects cultural property. It undertook to determine the guides or bases by which these engagements and cooperative actions are undertaken and how they can be used as indicators of future similar endeavors. In choosing these five(5) institutions, their history, mandate and functions, with their substantial physical environment, range of cultural property and status as national institutions were primary considerations. Their actions and participation can determine the success and sustainability, or failure of the proposed Heritage Zone. Such alliances and partnerships were also seen as being extended to working relations with the government. With the research objectives of this Study, meaningful and substantial participation of stakeholders are key. For this, the Study also contemplated the concerns, constraints and willingness of the institutions, as well as of the government. Research efforts focused on how their properties and the protection and stewardship thereof are intertwined or merged with both their external physical environment, e.g. the common shared public space and urban commons. To this end, the Study also looked into other possible outcomes including alternative approaches and results for heritage-oriented conservation, stewardship and partnerships in Ermita, Manila through designated historic areas such as the Heritage Zone.
Thesis (M.A. Urban and Regional Planning)--University of the Philippines Diliman
Keywords: Historic preservation -- Philippines -- Ermita (Manila).; Historic districts -- Philippines -- Ermita (Manila).; Historic sites -- Philippines -- Ermita (Manila).